Effect of friction on oxidative graphite intercalation and high-quality graphene formation - Steffen Seiler (Nature Portfolio, 2018)
Scalable graphene production from graphite via an intercalation-oxidation-reduction process is still hampered by low reproducibility and many lattice defects. Here, the authors show that reducing molecular friction by using highly crystalline graphite and mild oxidizing conditions is the key to high quality graphene.